CYRA: A Model-Driven CYber Range Assurance Platform - Michail Smyrlis; Iason Somarakis; George Spanoudakis; George Hatzivasilis; Sotiris Ioannidis (Applied Sciences, 2021)
Digital technologies are facilitating our daily activities, and thus leading to the social transformation with the upcoming 5G communications and the Internet of Things. However, mainstream and sophisticated attacks are remaining a threat, both for individuals and organisations. Cyber Range emerges as a promising solution to effectively train people in cybersecurity aspects. A Training Programme is considered adequate only if it can adapt to the scope of the attacks they cover and if the trainees apply the learning material to the operational system. Therefore, this study introduces the model-driven CYber Range Assurance platform (CYRA). The solution allows a trainee to be trained for known and new cyber-attacks by adapting to the continuously evolving threat landscape and examines if the trainees transfer the acquired knowledge to the working environment. Furthermore, this paper presents a use case on an operational backend ICT system, showing how the CYRA platform was utilised to increase the security posture of the organisation.